Political rhetoric in public speaking: stylistic analysis of selected polical speeches - Makoro, Seshego John (My University, 2018)
This study contributes to the rekindled interest in rhetoric in the 21st century, with the rise of important politicians on the world stage. It investigates the different rhetorical devices used by politicians to get their audiences to consent to their ideas. Selected political speeches analysed in this study highlight the different rhetorical techniques used by notable politicians in public speaking platforms. These techniques include the use of plural pronouns, repetition, allusion, rhetorical questions, negation, comparatives, present and future tense, hyperbole, and personification. The political speeches analysed here are Barack Obama’s inauguration speech (2009), Nelson Mandela’s inauguration speech (1994), Thabo Mbeki’s “I am an African” speech (1996), Muhammadu Buhari’s inauguration speech (2015), and Mmusi Maimane’s SONA Debate speech (2015). The study found that all the five speeches make use of the identified rhetorical devices to ‘sell’ their ideas to their listeners and canvass their support. The study clarifies the concept of rhetoric in public speaking and also explains why people (listeners) may be persuaded by politicians to ‘buy’ their ideas, conveyed through manipulative political language. It is imperative that people be made aware of the influence that political rhetoric could have on their decision-making, particularly when public opinion is formed regarding events announced on public media. Members of the public or prospective voters will be able to distinguish the truth from falsehood, if they are familiar with the elements of rhetoric in political speeches. Politicians are likely to be stopped in their tracks from betraying public trust for personal gains. It is also important to realise that there is nothing wrong if politicians apply rhetoric in public speaking, as long as they have no intention of deceiving the listeners. However, modern-day politicians seem to use it differently. This study has identified various rhetorical devices used in the selected speeches that provide some understanding of how other terms such as persuasion and manipulation are related to rhetoric.Key words: language and power, manipulation, persuasion, politicians, political rhetoric, public speaking.
Thesis (M. A. (English Studies)) --University of Limpopo, 2018
Keywords: Language and power; Manipulation; Politicians; Political rhetoric; Public speaking; Persuasion; Public speaking; Politicians